Media Use of Young Children: The Perceptions of Public Health Nurses Working in Child Health Clinics - Utriainen, Siiri; Vehviläinen‐Julkunen, Katri; Lamminpää, Reeta (Public health Nursing, 2025)
ABSTRACT Objective To describe the perceptions of public health nurses (PHNs) working in child health clinics on media use of young children and to investigate what are the perceptions of PHNs on adults’ role in young children's media use. Design An electronic cross‐sectional survey with Likert‐scaled and open‐ended questions. Sample The total of 183 PHNs working in Finnish child health clinics. Measurements Statistical descriptive analysis for Likert‐scaled questions and thematic analysis for open‐ended questions were used. Results Most (96.7%) PHNs agreed that media use was very common among young children. According to PHNs, the negative impacts of media use of young children included social, physical, and psychological impacts. The positive impacts included learning, communication, and access to information. PHNs stated that parents were most responsible for intervening in media use of young children, but PHNs have an important role in counseling families on it. Most PHNs (80.9%) stated that parents did not control media use of their children effectively. Conclusions PHNs are aware of impacts of media use and its prevalence among young children. They agree to have an important role in counseling families in it. More work in research is needed to improve PHNs’ expertise and resources for them to be able to guide families in young children's media use. A wider perspective from other health care professionals working with families should be studied to constitute multi‐professional understanding.